2020
DOI: 10.1152/ajprenal.00498.2019
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect on podocyte number in experimental diabetic nephropathy resulting from combined atrasentan and RAAS inhibition therapy

Abstract: Podocyte loss and proteinuria are both key features of human diabetic nephropathy (DN). The leptin-deficient BTBR mouse strain with the ob/ob mutation develops progressive weight gain, type 2 diabetes, and diabetic nephropathy that has many features of advanced human DN, including increased mesangial matrix, mesangiolysis, podocyte loss, and proteinuria. Selective antagonism of the endothelin-1 type A receptor (ETAR) by atrasentan treatment in combination with renin-angiotensin-aldosterone system inhibition wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Several studies suggested that the presence of PECs on the glomerular tuft represents an attempt to replenish the podocyte pool (Romoli et al, 2018;Lasagni et al, 2015;Peired et al, 2013;Kaverina et al, 2019;Eng et al, 2015;Zhang et al, 2013;Kaverina et al, 2020). The capacity of a PEC subset to differentiate into podocytes and restore the podocyte number is the likely explanation for the clinical observations of remission and regression of functional parameters of chronic kidney disease in patients with diabetic and nondiabetic nephropathies (Cortinovis et al, 2016;Fioretto et al, 1998;Remuzzi et al, 2006;Takahashi et al, 2007), as well as for podocyte number restoration observed in response to pharmacological treatment in experimental models of diabetic and non-diabetic kidney disease (Zhang et al, 2012;Hudkins et al, 2020;Zhang et al, 2015). Recent results elucidated the podocyte-progenitor cross-talk revealing mediators of progenitor quiescence during homeostasis and mechanisms by which podocyte loss triggers the activation of the progenitor population in the setting of podocyte injury (Peired et al, 2021).…”
Section: Why-experimental Evidencementioning
confidence: 99%
“…Several studies suggested that the presence of PECs on the glomerular tuft represents an attempt to replenish the podocyte pool (Romoli et al, 2018;Lasagni et al, 2015;Peired et al, 2013;Kaverina et al, 2019;Eng et al, 2015;Zhang et al, 2013;Kaverina et al, 2020). The capacity of a PEC subset to differentiate into podocytes and restore the podocyte number is the likely explanation for the clinical observations of remission and regression of functional parameters of chronic kidney disease in patients with diabetic and nondiabetic nephropathies (Cortinovis et al, 2016;Fioretto et al, 1998;Remuzzi et al, 2006;Takahashi et al, 2007), as well as for podocyte number restoration observed in response to pharmacological treatment in experimental models of diabetic and non-diabetic kidney disease (Zhang et al, 2012;Hudkins et al, 2020;Zhang et al, 2015). Recent results elucidated the podocyte-progenitor cross-talk revealing mediators of progenitor quiescence during homeostasis and mechanisms by which podocyte loss triggers the activation of the progenitor population in the setting of podocyte injury (Peired et al, 2021).…”
Section: Why-experimental Evidencementioning
confidence: 99%
“…Since it is known that the enlargement of SPS increases the mechanical forces exerted on podocytes by water filtration and induces podocyte detachment from the glomerular basement membrane [14] and that BTBR ob/ob mice were characterised by a significant loss of podocytes [19,20,24,25], we then identified and analysed the ultrastructure In diabetic mice, the mean SPS area per podocyte was significantly higher than in BTBR WT mice (Figure 6H) and was almost seven times higher than in the control WT group.…”
Section: Se-sem Ultrastructural Analysis In Btbr Ob/ob Micementioning
confidence: 99%
“…Since it is known that the enlargement of SPS increases the mechanical forces exerted on podocytes by water filtration and induces podocyte detachment from the glomerular basement membrane [14] and that BTBR ob/ob mice were characterised by a significant loss of podocytes [19,20,24,25], we then identified and analysed the ultrastructure of these cells in BTBR ob/ob mice. Consistent with previous data [26], diabetic BTBR ob/ob mice were characterised by hypertrophic changes in podocytes.…”
Section: Se-sem Ultrastructural Analysis In Btbr Ob/ob Micementioning
confidence: 99%
“…Injuries to podocytes are considered an important contributor to diabetic kidney disease progression toward end-stage kidney disease [39][40][41]. Suganami et al reported the prevention and reversal of renal injury by leptin administration in animal models of diabetic nephropathy [39].…”
Section: Regulators Of Glomerular Progenitor Physiology: When the Orchestra Tunes The Melodymentioning
confidence: 99%
“…In particular, the leptin treatment, but not RAAS-I, resulted in a significant increase in podocyte density and number and in an increase of WT1-positive proliferating PEC. The mechanisms underlying this process was further delineated in a follow-up paper, where they showed that a dual treatment of leptin-deficient ob/ob mice with a selective antagonist of the endothelin-1 type A receptor (ETAR) in combination with RAAS inhibition led to an improved phenotype [40], characterized by the activation of PECs and increased number of podocytes. These results provide indirect evidence that PECs may be a potential reservoir to restore lost podocytes and that the differentiative capacity of PECs may be a key element for the regression of diabetic nephropathy that might be pharmacologically modulated.…”
Section: Regulators Of Glomerular Progenitor Physiology: When the Orchestra Tunes The Melodymentioning
confidence: 99%